2019
DOI: 10.1530/jme-17-0314
|View full text |Cite
|
Sign up to set email alerts
|

The molecular pathways underlying early gonadal development

Abstract: The body of knowledge surrounding reproductive development spans the fields of genetics, anatomy, physiology and biomedicine, to build a comprehensive understanding of the later stages of reproductive development in humans and animal models. Despite this, there remains much to learn about the bi-potential progenitor structure that the ovary and testis arise from, known as the genital ridge (GR). This tissue forms relatively late in embryonic development and has the potential to form either the ovary or testis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 189 publications
(253 reference statements)
0
31
0
Order By: Relevance
“…Subsequently, by five weeks post-conception, primordial germ cells migrate from the yolk sac to the urogenital ridge. Several genes including NR5A1 (also known as SF1), WT1, EMX2, and LHX9 are required for the formation of the bipotential gonadal ridge in humans [5,6].…”
Section: Gonadal and Germ Cell Developmentmentioning
confidence: 99%
“…Subsequently, by five weeks post-conception, primordial germ cells migrate from the yolk sac to the urogenital ridge. Several genes including NR5A1 (also known as SF1), WT1, EMX2, and LHX9 are required for the formation of the bipotential gonadal ridge in humans [5,6].…”
Section: Gonadal and Germ Cell Developmentmentioning
confidence: 99%
“…The formation of sexual dimorphism involves critical and pervasive events in sexually reproducing animals, thereby ensuring reproductive success. The gonads play a central role in such processes, because their differentiation into either ovaries or testes subsequently dictates the overall sex characteristics of the individual by regulating development of the external and internal sex organs and the brain via sex hormones (Capel, 2017;Yang et al, 2018). The embryonic gonads initially form as sexually bipotent structures known as genital ridges (GRs), which consist of GR progenitor cells (GPCs).…”
Section: Introductionmentioning
confidence: 99%
“…Although most previous studies have focused on the cellular, genetic, and epigenetic cues that direct the formation of gonadal sexual dimorphism from GRs (Capel, 2017), the ontogeny of bipotential gonads and the accompanying molecular events driving their development remain poorly understood, particularly in humans and non-human primates. The formation of the GR starts around embryonic day (E) 10.5 through the proliferation of the coelomic epithelium (CE) at the ventromedial aspect of mesonephros, a process that appears to be accompanied by the dissolution of basement membranes and the epithelial-tomesenchymal transition (EMT) (Karl and Capel, 1998;Kusaka et al, 2010;Yang et al, 2018). Prior studies have identified key genetic determinants of nascent GR formation, including Gata4, Nr5a1, Lhx9, Emx2, Six1/4, Cbx2, and Tcf21 (Birk et al, 2000;Cui et al, 2004;Fujimoto et al, 2013;Hu et al, 2013;Kusaka et al, 2010;Luo et al, 1994;Miyamoto et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…During embryonic stages in mammals, the gonadal ridge develops as a thickening of the coelomic epithelium, on the ventromedial surface of the mesonephric kidney, marking the formation of the gonadal primordium [ 18 ]. Coordinated proliferation of the coelomic epithelial cells, delamination and ingression of those cells results in the further development of the primordium [ 143 ]. In mammals, ingressing cells are the undifferentiated precursors of the supporting and steroidogenic cell lineages ( Figure 1 ) [ 17 ].…”
Section: Single-cell -Omics In Gonadal Development and Maturationmentioning
confidence: 99%